Chimerism in specimens referred to Saurophaganax maximus reveals a new species of Allosaurus (Dinosauria, Theropoda) - Danison, Andrew; Wedel, Mathew; Barta, Daniel; Woodward, Holly; Flora, Holley; Lee, Andrew; Snively, Eric (Vertebrate Anatomy Morphology Palaeontology, 2024)
Saurophaganax maximus is the designation of a massive theropod dinosaur recovered from the Kenton Member of the Upper Jurassic Morrison Formation in Oklahoma. The theropod was originally given the name Saurophagus maximus but was later revised to Saurophaganax maximus as the former did not conform to ICZN standards. Several autapomorphies were described for S. maximus including the postorbital lacking a postorbital boss, the atlas vertebra lacking facets for a proatlas, cervical vertebrae with nearly vertical postzygapophyses, unique accessory laminae on the holotype neural arch, pneumatized post-pectoral dorsal centra, laterally bowed femora, tibiae without an astragalar buttress and more prominent distomedial crest, less distally divergent fourth metatarsals, and craniocaudally expanded chevrons. However, our re-evaluation of these specimens shows that some of this material, including the holotype, is more parsimoniously referred to diplodocid sauropods found in the same quarry rather than an allosaurid. Because saurischian material referred to S. maximus is likely chimeric but diagnostic, we propose taxonomic revision and hypothesize dual validity. The name Saurophaganax maximus should refer to a previously undiagnosed diplodocid, instead of the large theropod recovered from the Kenton 1 Quarry. The presence of at least one skeletally mature theropod was confirmed through paleohistology of a fourth metatarsal. Despite the similarity of the theropod material to known species of Allosaurus, some decisively theropod specimens feature subtle autapomorphies that suggest a separate species, which we describe as Allosaurus anax sp. nov.